Nepali Expats Evacuation during Crises: Lessons Learnt and Way Forward - Khanal, Bharat (NCWA Annual Journal, 2025)
The study explores the evacuation operation for Nepali expats and draws insights into successful operation plans. It examines migration trends of Nepali nationals and assesses their vulnerability. The severity and complexity of migrants have greatly increased due to the unprecedented global milieu. The study suggests robust expat evacuation plans and mechanisms by analyzing the past evacuation operations that Nepal tackled. The research is based on a multidisciplinary approach, particularly quantitative content analysis, with few case studies and successful models from other countries being reviewed. The findings range from developing a crisis manual to proper coordination and institutionalization of legal and policy framework, and logistical arrangements. A draft framework model for effective evacuation operation is suggested for the safety and security of Nepali expatriates during a global crisis.